Measuring the Strength of UIN Sunan Ampel Surabaya in Achieving PTN-BH - Buchori, Imam; Muflihin, Mohammad Dliyaul; Junjunan, Mochammad Ilyas (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research focuses on assessing the strength of UIN Sunan Ampel Surabaya as one of the religious state universities with a public service agency towards an incorporated state university (PTN-BH). This research uses a qualitative approach by involving all components of the measurement indicators of the requirements as an incorporated state university, which are combined with qualitative data from observed respondents who understand the data conditions of UIN Sunan Ampel Surabaya. In addition, the benchmarking approach is used through visiting campuses to get expert judgment on indicators that cannot be quantified. The results of this study indicate that from the perspective of organizing quality tri dharma, the strength of UIN Sunan Ampel Surabaya is still not fully feasible to go to PTN-BH, while from the perspective of managing a state university organization based on good governance principles and the perspective of financial feasibility, UIN Sunan Ampel is already feasible to go to PTN-BH. In addition, from the total score value obtained, the accumulated strength of UIN Sunan Ampel Surabaya gets a value of 329.1 above the minimum value of eligibility to become a legal state university of 299.9.